2014
DOI: 10.3109/13880209.2014.929152
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage activation by polysaccharides fromAtractylodes macrocephalaKoidz through the nuclear factor-κB pathway

Abstract: Context: Atractylodes macrocephala Koidz is a traditional herb. Atractylodes macrocephalaon polysaccharides (AMP) have been found to enhance immunity and improve heart function. However, the mechanisms of the immunomodulatory effect have not been investigated. Objective: We examined whether AMP activated macrophages and explored the mechanisms of activation. Materials and methods: AMP was prepared and evaluated its immunomodulatory activity (25, 50, 100, and 200 lg/mL) by detecting the phagocytosis and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…All of these species contain at least 1 active ingredient from polysaccharides, flavonoids, or flavonoid glycosides. [21][22][23][24][25][26][27][28] In vivo and in vitro studies have shown that these bioactive components may augment the immune response, 27,28 enhance antioxidant abilities, 29,30 induce apoptotic pathways, 31 and suppress cancer cell migration. 32 Moreover, extractions of S. glabra and S. coicis may inhibit the activation of EBV 33 by eliminating free radicals, inducing the functional maturation of dendritic cells, and activating macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…All of these species contain at least 1 active ingredient from polysaccharides, flavonoids, or flavonoid glycosides. [21][22][23][24][25][26][27][28] In vivo and in vitro studies have shown that these bioactive components may augment the immune response, 27,28 enhance antioxidant abilities, 29,30 induce apoptotic pathways, 31 and suppress cancer cell migration. 32 Moreover, extractions of S. glabra and S. coicis may inhibit the activation of EBV 33 by eliminating free radicals, inducing the functional maturation of dendritic cells, and activating macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ is an important proinflammatory cytokine and plays a critical role in the immune and inflammatory response (Liu, Ho, & Mak, 2012). It has been reported that TNF-␣ can act on macrophages and monocytes in an autocrine manner to strengthen various functional responses and induce the expression of other immunoregulatory mediators (Ji, Chen, & Zheng, 2015). As shown in Fig.…”
Section: Ljp-31 Induces No Tnf-˛ Il-1ˇ Il-6 and Il-10 Production Bmentioning
confidence: 99%
“…When it is subjected to external stimuli (such as LPS), I κ B α phosphorylates, degrades, and dissociates from the NF- κ B/I κ B α complex [ 25 , 26 ]. The activated NF- κ B p65 following the translocation into the cell nucleus combines with the target gene promoter or enhancer [ 27 ]. It continued to rapidly induce the synthesis and transcription of target gene mRNA.…”
Section: Discussionmentioning
confidence: 99%